2021
DOI: 10.3389/fphar.2021.655865
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Network Meta-Analysis: Comparative Efficacy and Safety of Biosimilars, Biologics and JAK1 Inhibitors for Active Crohn Disease

Abstract: Background: Crohn disease (CD) is a chronic inflammatory disease that affects quality of life. There are several drugs available for the treatment of CD, but their relative efficacy is unknown due to a lack of high-quality head-to-head randomized controlled trials.Aim: To perform a mixed comparison of the efficacy and safety of biosimilars, biologics and JAK1 inhibitors for CD.Methods: We searched PubMed, Web of Science, embase and the Cochrane Library for randomized controlled trials (RCTs) up to Dec. 28, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Overall, our findings were supported by these studies. For example, one study in CD included patients treated with unlicensed dosages of upadacitinib (i.e., 3, 6, 12, or 24 mg two times a day and 24 mg QD), and reported that there were no statistically significant differences in the rates of any AE between upadacitinib and TNF blockers (adalimumab, certolizumab pegol, and infliximab), IL-12/23 receptor antagonist (ustekinumab), and integrin receptor antagonist (vedolizumab) [ 56 ]. Similarly, we reviewed one study in PsA [ 57 ] and one study in AD [ 58 ] which did not specify upadacitinib dosage and concluded that upadacitinib has comparable risk of MACE compared to TNF blockers (adalimumab, certolizumab pegol, etanercept, golimumab), IL-17A receptor antagonist (secukinumab), IL-23 receptor antagonist (guselkumab), and phosphodiesterase 4 inhibitor (apremilast).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings were supported by these studies. For example, one study in CD included patients treated with unlicensed dosages of upadacitinib (i.e., 3, 6, 12, or 24 mg two times a day and 24 mg QD), and reported that there were no statistically significant differences in the rates of any AE between upadacitinib and TNF blockers (adalimumab, certolizumab pegol, and infliximab), IL-12/23 receptor antagonist (ustekinumab), and integrin receptor antagonist (vedolizumab) [ 56 ]. Similarly, we reviewed one study in PsA [ 57 ] and one study in AD [ 58 ] which did not specify upadacitinib dosage and concluded that upadacitinib has comparable risk of MACE compared to TNF blockers (adalimumab, certolizumab pegol, etanercept, golimumab), IL-17A receptor antagonist (secukinumab), IL-23 receptor antagonist (guselkumab), and phosphodiesterase 4 inhibitor (apremilast).…”
Section: Discussionmentioning
confidence: 99%
“…Although no head‐to‐head randomized clinical trial of infliximab versus adalimumab was conducted in patients with IBD, multiple studies have shown comparable outcomes in patients with CD, including systematic reviews and network meta‐analysis (27,28). However, a specific study focusing on patients with fistulizing CD showed superiority of infliximab over adalimumab in inducing response and remission (29).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 15 observational studies, the risk of serious infection increased with the combination of anti-TNF and an immunosuppressive agent (in six cohorts; RR, 1.19; 95% CI, 1.03–1.37), especially in the case of anti-TNF and corticosteroids (in four cohorts; RR, 1.64; 95% CI, 1.33–2.03) or the use of all three drugs (in two cohorts; RR, 1.35; 95% CI, 1.04–1.77) compared to anti-TNF monotherapy [ 77 ]. A network meta-analysis of patients with active CD also showed no significant difference regarding the rate of adverse events and infections or serious/severe infections among biological/small molecule therapies (IFX, ADA, VDZ, UST, tofacitinib and CT-P13) [ 78 ].…”
Section: Medical Treatment For Fistulizing CDmentioning
confidence: 99%